Guanidine thiocyanate solution facilitates sample collection for plant rhizosphere microbiome analysis - Sun,Xiaoxiao; Wang,Meiling; Guo,Lin; Shu,Changlong; Zhang,Jie; Geng,Lili (PeerJ, 2019)
The interactions between rhizosphere microorganisms and plants are important for the health and development of crops. Analysis of plant rhizosphere bacterial compositions, particularly of those with resistance to biotic/abiotic stresses, may improve their applications in sustainable agriculture. Large-scale rhizosphere samplings in the field are usually required; however, such samples, cannot be immediately frozen. We found that the storage of samples at room temperature for 2 days leads to a considerable reduction in the operational taxonomic unit (OTU) number and the indices of bacterial alpha-diversity of rhizosphere communities. In this study, in order to overcome these problems, we established a method using guanidine thiocyanate (GTC) solution for the preservation of rhizosphere samples after their collection. This method allowed the maintenance of the samples for at least 1 day at room temperature prior to their cryopreservation and was shown to be compatible with conventional DNA isolation protocols. Illumina sequencing of V3 and V4 hypervariable regions of the 16S rRNA gene was used to assess the feasibility and reliability of this method, and no significant differences were observed in the number of OTUs and in the Chao and Shannon indices between samples stored at −70 °C and those stored in GTC solution. Moreover, the representation of Pseudomonas spp. in samples stored in GTC solution was not significantly different from that in samples stored at −70 °C, as determined by real-time quantitative polymerase chain reaction (p > 0.05). Both types of samples were shown to cluster together according to principal coordinate analysis. Furthermore, GTC solution did not affect the bacterial taxon profiles at different storage periods compared with those observed when storing the samples below −70 °C. Even incubation of thawed samples (frozen at −70 °C) for 15 min at room temperature induced minor changes in the bacterial composition. Taken together, our results demonstrated that GTC solution may provide a reliable alternative for the preservation of rhizosphere samples in the field.
Keywords: Guanidine thiocyanate; Plant rhizosphere microbiome; Rhizosphere sampling; 16S rRNA; Illumina MiSeq sequencing